2015
DOI: 10.1002/ppul.23218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of respiratory physiotherapy on gastro-oesophageal reflux in infants: A systematic review

Abstract: The evidence is not conclusive on whether respiratory physiotherapy induces or aggravates GOR in infants and small children. Age, disease, and treatment options play an important role. More specific research, also focussing on the influence of respiratory physiotherapy on non-acid reflux and the impact of recently developed airway clearance techniques (ACT's) on GOR is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Some authors claim that certain ACT's could exacerbate GOR and even suggest that postural drainage with a head‐down tilt is contra‐indicated in patients with GOR . Our group found that intrapulmonary percussive ventilation (IPV) in upright position does not induce, nor aggravate GOR in infants without and with pathological GOR, respectively …”
Section: Introductionmentioning
confidence: 73%
“…Some authors claim that certain ACT's could exacerbate GOR and even suggest that postural drainage with a head‐down tilt is contra‐indicated in patients with GOR . Our group found that intrapulmonary percussive ventilation (IPV) in upright position does not induce, nor aggravate GOR in infants without and with pathological GOR, respectively …”
Section: Introductionmentioning
confidence: 73%
“…Previously no benefit has been reported from chest physiotherapy techniques using postural drainage combined with clapping or passive expiratory manoeuvres in children hospitalized for bronchiolitis . The use of postural drainage with head‐down tilt could exacerbate gastro‐oesophageal reflux (GOR) and is contra‐indicated in patients with GOR …”
Section: Discussionmentioning
confidence: 99%
“…The few studies concerning chest physiotherapy and its effect on GOR mainly focus on positioning the child with head‐down tilt and are using traditional techniques like percussion, vibrations, chest clapping, and thoracic compression as treatment modalities . More prudence seems justified while treating very young children suffering from pathological GOR or a chronic disease (e.g., infants with CF), especially when combining with gravity‐assisted positions . It is well known that posture has an impact on the frequency of LOS relaxations, one of the physiological mechanisms to increase GOR episodes .…”
Section: Discussionmentioning
confidence: 99%
“…18,[24][25][26] More prudence seems justified while treating very young children suffering from pathological GOR or a chronic disease (e.g., infants with CF), especially when combining with gravity-assisted positions. 27 It is well known that posture has an impact on the frequency of LOS relaxations, one of the physiological mechanisms to increase GOR episodes. 28 In infants with symptoms attributed to GOR, prone and left lateral position produced a significant reduction in total GOR, compared to supine and right lateral position.…”
Section: Discussionmentioning
confidence: 99%